The Relationship Between Essential Skills and Perceived Employability: A Case Study of Malaysian Technical University Network Undergraduates - Mohd Taufik Won, Ereen Syafiqa Won; Mohd Nor, Norasmiha (Research in Management of Technology and Business, 2026)
In today’s competitive job market, academic qualifications alone are no longer sufficient to guarantee graduate employability, highlighting the growing importance of essential skills among university graduates. Therefore, this study aims to examine the influence of technical skills, soft skills and social mobility skills on the perceived employability of final-year students from Malaysian Technical University Network (MTUN) universities. A quantitative research approach was employed, whereby data were collected through an online questionnaire using quota sampling to ensure representation across the selected universities. The collected data were analysed using the Statistical Package for the Social Sciences (SPSS), involving descriptive statistics, reliability analysis, normality testing and correlation analysis. The findings reveal that technical skills, soft skills and social mobility skills are significantly related to perceived employability among final-year students. Students who demonstrated stronger technical competencies, effective communication skills, adaptability and social awareness reported higher confidence in their readiness to enter the workforce. These findings indicate that graduate employability is shaped not only by academic achievement but also by the development of practical and transferable skills relevant to real-world work environments.